Nanoarchitectonics-based model membrane platforms for probing membrane-disruptive interactions of odd-chain antimicrobial lipids - Yoon, Bo Kyeong (2023)
The use of nanoscience tools to investigate how antimicrobial lipids disrupt phospholipid membranes has greatly advanced molecular-level biophysical understanding and opened the door to new application possibilities. Until now, relevant studies have focused on even-chain antimicrobial lipids while there remains an outstanding need to investigate the membrane-disruptive properties of odd-chain antimicrobial lipids that are known to be highly biologically active. Herein, using the quartz crystal microbalance-dissipation (QCM-D) and electrochemical impedance spectroscopy (EIS) techniques, we investigated how an 11-carbon, saturated fatty acid and its corresponding monoglyceride-termed undecanoic acid and monoundecanoin, respectively-disrupt membrane-mimicking phospholipid bilayers with different nanoarchitectures. QCM-D tracking revealed that undecanoic acid and monoundecanoin caused membrane tubulation and budding from supported lipid bilayers, respectively, and were only active above their experimentally determined critical micelle concentration (CMC) values. Monoundecanoin was more potent due to a lower CMC and electrochemical impedance spectroscopy (EIS) characterization demonstrated that monoundecanoin caused irreversible membrane disruption of a tethered lipid bilayer platform at sufficiently high compound concentrations, whereas undecanoic acid only induced transient membrane disruption. This integrated biophysical approach also led us to identify that the tested 11-carbon antimicrobial lipids cause more extensive membrane disruption than their respective 12-carbon analogues at 2 × CMC, which suggests that they could be promising molecular components within next-generation antimicrobial nanomedicine strategies.